Hubungan Pengetahuan Ibu Tentang Manajemen Laktasi Dengan Perilaku Dalam Pemberian Asi di Kecamatan Belopa - Asri, Muhammad; Muzfa, A. Wardah; Jannah, Miftahul (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Implementation of breastfeeding can be done well and correctly if there is complete information about the benefits of breast milk and breastfeeding as well as lactation management. Exclusive breastfeeding can be hampered by several things such as the mother's low level of knowledge and the incessant marketing of formula milk, lack of support from health workers, and the factor of the mother working as a farmer, trader, civil engineer or private worker (Dinkes, 2008). This study aims to determine the relationship between maternal knowledge about lactation management and behavior in breastfeeding in Belopa District.The type of research used is descriptive research using a correlation analytical research design. The research design used was a cross sectional approach. The sample in this study was breastfeeding mothers aged 26 – 55 years with a total of 37 respondents or samples. The research results showed that there was a relationship between maternal knowledge about lactation management and behavior in breastfeeding in Belopa District with chi-square test results of p = 0.002 (p < 0.05). Expected on the agencies to provide counseling to the breastfeeding mothers about the importance of maternal knowledge about lactation management and behavior in breastfeeding.Implementation of breastfeeding can be done well and correctly if there is complete information about the benefits of breast milk and breastfeeding as well as lactation management. Exclusive breastfeeding can be hampered by several things such as the mother's low level of knowledge and the incessant marketing of formula milk, lack of support from health workers, and the factor of the mother working as a farmer, trader, civil engineer or private worker (Dinkes, 2008).This study aims to determine the relationship between maternal knowledge about lactation management and behavior in breastfeeding in Belopa District.The type of research used is descriptive research using a correlation analytical research design. The research design used was a cross sectional approach. The sample in this study was breastfeeding mothers aged 26 – 55 years with a total of 37 respondents or samples.The research results showed that there was a relationship between maternal knowledge about lactation management and behavior in breastfeeding in Belopa District with chi-square test results of p = 0.002 (p < 0.05).Expected on the agencies to provide counseling to the breastfeeding mothers about the importance of maternal knowledge about lactation management and behavior in breastfeeding.